Increasing Income Through The Impact Of A Creative Economy Based On Local Cultural Values - Bashir ldao Machesa (International Forum of Researchers and Lecturers, 2025)
This research explores how local cultural values ​​can be the basis for creative economic growth and increased income in a region. Through an interdisciplinary approach, this research investigates the impact of a creative economy enriched by local wisdom, highlighting how creative and innovative aspects of traditional culture can generate sustainable business opportunities. By using case studies and quantitative data analysis, this research shows the relationship between a creative economy that is rooted in local cultural values ​​and increasing people's income. The results of this research provide valuable insights for the development of sustainable and inclusive local economic policies.